Rol del trabajador social en la situación de abandono del adulto mayor en el cantón Santa Rosa-2022 - Ramírez Tuarez, Gabriela Silvania; Yanes Fernández, Anggie Stephania (Machala: Universidad Técnica de Machala, 2023)
The present research has developed a comprehensive proposal to address the problem of abandonment of older adults in the Santa Rosa Canton. Our research is based on a deep understanding of the situation of abandonment of older adults, supported by a solid theoretical foundation that highlights the importance of comprehensive care and community participation. The main objective of this research focuses on strengthening capabilities and approaches in the field of social work, with the purpose of improving the quality and effectiveness of the interventions carried out by professionals. The main focus lies on optimizing existing practices and developing innovative strategies to more effectively address social problems and the needs of the groups and communities served. Through this study, we seek to raise the quality of the services provided, promoting a positive impact on the lives of beneficiaries and contributing to social well-being in general. The research study is framed in the methodology with hermeneutical and descriptive elements due to the complex nature of the problem of abandonment of older adults. The decision to use a hermeneutic approach is based on the need to understand the subjective experiences of older adults, their experiences and perceptions. Through this approach, we seek to go beyond quantitative data and delve into individual narratives and perspectives. Furthermore, the descriptive approach is adopted to analyze in detail the different dimensions of the problem. The combination of these approaches will allow us to obtain a complete and enriching understanding of the situation of abandonment of older adults in the Santa Rosa Canton. Our structural components have been designed to address each of these objectives, including mobilizing financial resources, providing nutritious snacks, organizing recreational activities, raising community awareness, and continuous impact evaluation. Furthermore, we have confirmed that awareness-raising and community communication are key tools to generate a change in attitude and awareness in society regarding the abandonment of older adults. The active dissemination of information and raising awareness has led to a greater understanding of the problem and an increase in community participation in solving this social problem. During the implementation of our proposal, we have managed to raise significant funds, provide nutritious food, organize recreational and social activities, and raise awareness in the community about the problem of abandonment of older adults. These achievements align with our theoretical bases and support the importance of comprehensive care and community participation in improving the quality of life of older adults. In conclusion, our proposal represents an important step towards comprehensive care for older adults in situations of abandonment in the Santa Rosa Canton. We have shown that, with the collaboration of volunteers and active community participation, it is possible to provide significant support to this vulnerable population and improve their physical and emotional well-being.
La presente investigación se ha desarrollado una propuesta integral para abordar la problemática del abandono de adultos mayores en el Cantón Santa Rosa. Nuestra investigación se fundamenta en la comprensión profunda de la situación de abandono de adultos mayores, respaldada por una base teórica sólida que destaca la importancia de la atención integral y la participación comunitaria. El objetivo principal de esta investigación se centra en el fortalecimiento de las capacidades y enfoques en el campo del trabajo social, con el propósito de mejorar la calidad y eficacia de las intervenciones realizadas por los profesionales. El enfoque principal radica en optimizar las prácticas existentes y desarrollar estrategias innovadoras para abordar de manera más efectiva las problemáticas sociales y las necesidades de los grupos y comunidades atendidas. A través de este estudio, se busca elevar la calidad de los servicios brindados, promoviendo un impacto positivo en la vida de los beneficiarios y contribuyendo al bienestar social en general. El estudio de la investigación se enmarca en la metodología es los elementos de hermenéuticos y descriptivos debido a la naturaleza compleja de la problemática del abandono de adultos mayores. La decisión de utilizar un enfoque hermenéutico se basa en la necesidad de comprender las experiencias subjetivas de los adultos mayores, sus vivencias y percepciones. A través de este enfoque, buscamos ir más allá de los datos cuantitativos y sumergirnos en las narrativas y perspectivas individuales. Además, el enfoque descriptivo se adopta para analizar en detalle las diferentes dimensiones de la problemática. La combinación de estos enfoques nos permitirá obtener una comprensión completa y enriquecedora de la situación de abandono de los adultos mayores en el Cantón Santa Rosa. Nuestros componentes estructurales se han diseñado para abordar cada uno de estos objetivos, incluyendo la movilización de recursos financieros, la provisión de refrigerios nutritivos, la organización de actividades recreativas, la sensibilización comunitaria y la evaluación continua de impacto. Además, hemos constatado que la sensibilización y la comunicación comunitaria son herramientas clave para generar un cambio de actitud y conciencia en la sociedad sobre el abandono de adultos mayores. La difusión activa de información y la creación de conciencia han llevado a una mayor comprensión de la problemática y a un aumento en la participación de la comunidad en la solución de este problema social. Durante la implementación de nuestra propuesta, hemos logrado recaudar fondos significativos, proporcionar alimentos nutritivos, organizar actividades recreativas y sociales, y sensibilizar a la comunidad sobre la problemática del abandono de adultos mayores. Estos logros se alinean con nuestras bases teóricas y respaldan la importancia de la atención integral y la participación comunitaria en la mejora de la calidad de vida de los adultos mayores. En conclusión, nuestra propuesta representa un paso importante hacia la atención integral de los adultos mayores en situación de abandono en el Cantón Santa Rosa. Hemos demostrado que, con la colaboración de voluntarios y la participación activa de la comunidad, es posible brindar un apoyo significativo a esta población vulnerable y mejorar su bienestar físico y emocional.
Keywords: ADULTO MAYOR; TRABAJO SOCIAL; ABANDONO; INTERVENCION